MENINGKATKAN KEMAMPUAN BERBICARA BAHASA INGGRIS MELALUI PERMAINAN BAHASA (LANGUAGE GAMES) - Pakaya, Marina (JURUSAN MANAJEMEN PENDIDIKAN ISLAM, 2014)
A game in language is an effective tool that increase the learning enthusiasm of the students. It becomes a way to make the learning joyful. This research employs a qualitative approach that describes the game. The result shows that there were 30 students in class B joined the written test, there were 8 students (27%) who got A, 15 students (50%) who got B, 6 students (20%) who got C, and 1 student (3%) who did not pass the written text. So there were 17 students who failed in the oral text.